If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + 7 = 3(4 + -1q) Reorder the terms: 7 + 5p = 3(4 + -1q) 7 + 5p = (4 * 3 + -1q * 3) 7 + 5p = (12 + -3q) Solving 7 + 5p = 12 + -3q Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 5p = 12 + -7 + -3q Combine like terms: 7 + -7 = 0 0 + 5p = 12 + -7 + -3q 5p = 12 + -7 + -3q Combine like terms: 12 + -7 = 5 5p = 5 + -3q Divide each side by '5'. p = 1 + -0.6q Simplifying p = 1 + -0.6q
| 4n-5=3 | | x*x-18x+81=4+81 | | -14=-(-2+2) | | -x*x+x+.25=1.25 | | 2m+6=2(2m+3)-2 | | -x*-x+x+.25=1.25 | | 3(c-8)+13=5c+5 | | -4.4=2x+25.6 | | 4.2z=-4(0.6-1.2) | | 2mx^2-mx+1=0 | | 3(6-x)-8=2 | | 5x+6x-64=3x-65 | | 4v-2=10 | | 5x^2=2x+1 | | 6x+19x=25 | | 4x+2+6x-1=13x+1 | | 18-6y=0 | | 4x+3=42 | | 10=3f+1 | | 2b+1=7 | | 4x-5=-1x-30 | | -2x-10+7x=6x+14-4x | | x+14=-32-9 | | -6y+13=-5(y-4) | | 13x=-7-3-20 | | 4x+3x=-35 | | Y+13-7y=-5(y-4) | | 16x+2=-17 | | 22-5x+9x=-2(-6x+5) | | 3y^2+z= | | -33-6y+19=-23y+56+7y | | 7(x+2)=5x+2+6x |